Difficult Interpersonal Encounters with Medical Students and Residents: Two Objective Standardized Teaching Encounters - Nicole Jones; Liana Milanes; Vanessa Banales; Iris Price; Ivan Gomez; Susan Hughes (Association of American Medical Colleges, 2017)
Introduction Objective standardized teaching exercises (OSTEs) are widely used to develop professional competencies, especially in the health care professions. An OSTE involves exposing different providers to the same, time-limited scenario that is concurrently observed and/or recorded for either formative or summative evaluation. As there are limited resources available for creating a resident-specific OSTE, especially those applicable to family and community medicine residents, we created and evaluated a resident OSTE (R-OSTE) for second- and third-year family and community medicine residents. Methods This R-OSTE involved two cases. The first featured Taylor, a third-year medical student resistant to feedback. The second featured Kris, a first-year resident nervous about approaching the attending on duty. Our R-OSTE had residents teaching interpersonal skills to trained actors in a standardized learner role. Results Residents in the teaching role were formatively evaluated by peer observers (fellow residents) and standardized learners on interpersonal domains such as communication and professionalism. Learners gave residents an average performance rating of 4.9 on a 1 to 6 scale with 1 = Very Poor and 6 = Excellent. Residents also evaluated the OSTE itself, rating their experience on multiple teaching-related statements. Eighty-six percent of residents agreed this exercise was an appropriate development activity for family medicine residents. Overall, our R-OSTE was rated highly for relevance to teaching by the residents. Discussion The residents were rated highly by both peer observers and standardized learners. However, there was little variability in peer observer scores, indicating the need for an alternative method of measurement.